Decoding Rainfall Diversity: A Long-Term GIS Assessment of the Chikkamagaluru Region - Sreekeshava, K.S.; Bhargavi, C.; Gayathri, G. (Journal of Environmental Science and Engineering Technology, 2025)
This study analyses long-term rainfall variability across Chikkamagaluru, Mudigere and Belur taluks using a 47-year continuous dataset (1977–2024). Spatial interpolation (Ordinary Kriging, 1 km × 1 km resolution) and temporal trend diagnostics (Mann–Kendall, Sen’s slope) were used to quantify seasonal patterns and windward–leeward gradients. Mean annual rainfall across the region is 1769 mm, with monsoon rainfall contributing 80–86% of yearly totals. Windward stations such as Kottigehara and Hosakere receive 3–4 times more rainfall (up to 4170 mm) than leeward stations such as Kalasapura (~680 mm). Trend analysis indicates weak but notable seasonal trends: monsoon rainfall shows non-significant decreasing tendencies at most leeward stations, while pre-monsoon rainfall shows slight increasing trends (Sen’s slope +1.8 to +3.2 mm/year). Spatial rainfall maps and trends align strongly with Western Ghats orography and established monsoon climatology. These findings enhance hydro-climatic understanding and provide actionable insights for watershed planning, agriculture, and hazard mitigation.